Analysis of the perception of teachers and students on the use of traditional and innovative teaching methodologies in higher education (GEON Journal (Management, Organizations and Business), 2021)
The valuation of qualitative variables in teaching-learning strategies is a key factor in the development of educational strategies that strengthen learning, supported by ICT. This strengthening includes the application of innovative methodologies and didactic activities to achieve a better transmission and reception of knowledge. The objective of this research is to evaluate a technological acceptance model (TAM) based on a questionnaire addressed to teachers and students of a public institution of higher education in Medellin, Colombia, to determine the level of incidence of the variables: attitude, perceived utility, ease of use, intention and confidence, in comparison to didactic methodologies. We present a descriptive research supported by validation techniques and methods such as the Bartlett test, KMO, Cronbach's Alpha and the convergent and discriminant validation for the constructs of the model. As a result, the degree of favorability in the perceived relevance for both traditional and innovative trends is presented, evidencing a positive association between the construct variables studied without detriment or harm in the existence of putting into action an innovative tool within the classroom.
Keywords: Economic and financial education; education; information and communication technologies; learning strategies; methodologies; validity; reliability